Risk Factors, Antithrombotic Management, and Long-Term Outcomes of Patients Undergoing Endovascular Treatment of Unruptured Intracranial Aneurysms - Xiang, Yanxiao; Zhang, Ping; Lai, Yongjie; Wang, Donghai; Liu, Anchang (Thrombosis and Haemostasis, 2024)
Background Patients receiving endovascular treatment for unruptured intracranial aneurysms (UIAs) face varying risks and benefits with antithrombotic management. This study aimed to evaluate the perioperative and long-term effects of antithrombotic strategies, identify the populations that would benefit, and explore the predictive factors affecting the long-term outcomes.Methods UIA patients undergoing endovascular treatment including stent-assisted coiling or flow diversion between June 2019 and June 2022 were enrolled. We compared perioperative and long-term complications between tirofiban and dual antiplatelet therapy groups. Optimal candidates for each antithrombotic treatment were identified using multivariate logistic regression. Nomograms were developed to determine the significant predictors for thromboembolic complications during follow-up.Results Among 181 propensity-score matched pairs, the tirofiban group showed a trend toward a lower rate of thromboembolic complications than the DAPT group without elevating major bleeding risk in either period. Homocysteine (Hcy) level ≥10 μmol/L was a significant independent factor associated with thromboembolic complication in both periods. Subgroup analysis highlighted that in patients with high Hcy levels, tirofiban and sustained antiplatelet treatment for ≥12 months were protective factors, while a history of stroke was an independent risk factor for thromboembolic events in follow-up. Four variables were selected to construct a prognostic nomogram, history of hypertension, prior stroke, Hcy level, and the duration of antiplatelet therapy.Conclusion Perioperative low-dose tirofiban and extended antiplatelet therapy demonstrated a favorable trend in long-term outcomes for UIA patients with preoperative Hcy levels ≥10 μmol/L undergoing endovascular treatment. The prognostic model offers reliable risk prediction and guides antithrombotic strategy decisions.
Keywords: unruptured intracranial aneurysms; endovascular treatment; antithrombotic strategies; long-term outcomes